1971
DOI: 10.1159/000122009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Catechol and Indole Amines upon Pineal Uptake of Thyroxine

Abstract: Bovine pineal slices were incubated in Krebs-Ringer phosphate buffer together with 125I-thyroxine and varying concentrations of epinephrine, norepinephrine, serotonin, melatonin, TSH, and aldosterone. Norepinephrine in concentrations of 10–5 m and 10–6 m significantly (p = 0.01, 0.05) decreased the uptake of thyroxine by the pineal slices, whereas epinephrine at 10–5 m slightly increased (p = 0.l0) the uptake. Melatonin at 10–3 m increased the uptake of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Direct effects o f melatonin on pineal cells are suggested by the observation that the pineal gland exhibits the highest uptake of (3H)-melatonin 1 h after its intravenous administration to cats (Wurtman et al, 1964). Likewise incubation of bovine pineal slices with melatonin has been shown to enhance pineal thyroxine uptake, an effect not shared by its closely related compound serotonin (Cady and Dillman, 1971). The present report describes the occurrence o f melatonin-binding sites in membrane preparations from bovine pineal gland.…”
Section: Introductionmentioning
confidence: 52%
“…Direct effects o f melatonin on pineal cells are suggested by the observation that the pineal gland exhibits the highest uptake of (3H)-melatonin 1 h after its intravenous administration to cats (Wurtman et al, 1964). Likewise incubation of bovine pineal slices with melatonin has been shown to enhance pineal thyroxine uptake, an effect not shared by its closely related compound serotonin (Cady and Dillman, 1971). The present report describes the occurrence o f melatonin-binding sites in membrane preparations from bovine pineal gland.…”
Section: Introductionmentioning
confidence: 52%
“…In this context, Cady and Ddlmann [3] have shown that melatonin enhances the uptake of thyroxin by bovine pineal slices. Re cently we have presented results of a more elaborate study of the responses of pineal cells to melatonin microelectro phoresis [26], showing a pronounced circadian rhythm in the numers of excitatory and inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence point to a local, intrapineal, role of melatonin. The pineal gland has a high capacity to take up melatonin from the bloodstream (22), and melatonin treatments alter several pineal morphological and biochemical parameters, including the number of dense-cored or granulated vesicles (23,24), thyroxine uptake (25), microtubular protein content (26), enzyme activity in melatonin pathway (26)(27)(28) and noradrenaline (NA) release and uptake (29). It was also early noted that melatonin injections alter 5-HT levels and block the rhythm in 5-HT content of the rat and ferret pineal gland (30,31).…”
mentioning
confidence: 99%